Manejo da produção de raiz e colo em coentro (coriandrum sativum L.) - Rocha, Alex Oliveira (2017)
Coriander (Coriandrum sativum L.) is one of the main hardwoods produced in the rugged region of Alagoas. It is a seasoning olive grove that has antibacterial, antifungal and antioxidant properties. In recent years farmers in the region have faced reduced production due to death of seedlings, which have necrotic lesions in the cervix and roots. In recent works the pathogenicity of the following species found in association with diseased plants: Rhizoctonia solani, Pythium irregulare, Fusarium inflexum, F. lacertarum and F. falciforme have been demonstrated. However, their relative importance as phytopathogens was not estimated, nor were management alternatives prospected. Thus, the objectives of this work were: to verify the virulence of previously characterized phytopathogenic isolates and to evaluate the efficiency of two management strategies: genetic resistance of commercial varieties and use of solarizer for soil disinfestation. To this end, three distinct experiments were conducted. In the first one, the virulence of R. solani, P. irregulare, F. inflexum, F. lacertarum and F. falciforme to the Verdão variety was evaluated. In the second, the susceptibility of 7 commercial strains of coriander to the same isolates tested in the first experiment was estimated. And, in the third, the efficiency in reducing the occurrence of root rot and colon rot by means of thermal treatment of soil in solarizer was evaluated. For all experiments, the following variables were considered: preemergence damping-off, post-emergence damping-off, emergence, total matter fresh, matter fresh / plant, plant height, incidence and severity. There was a difference in virulence between isolates, being significantly the ones with the greatest virulence: P. irregulare and F. falciforme. Regarding the varieties, there was interaction between isolates versus varieties as a function of the variable analyzed. The use of the solar collector was efficient to reduce root rot and colon rot.